Information Security Management in a Higher Education Institution Based on Standards, Legal Basis for the Optimization of Administrative Resources - Andrade A, Diego; Toapanta T., Moisés; Durango, Rodrigo Del Pozo; Vanegas-Guillén, Oswaldo; Pavón, Pamela Toapanta; Gómez D. , Zharayth; Maciel A. , Roció; Orizaga T, Antonio (Journal of Ecohumanism, 2024)
Problems in managing information security for access to remote laboratories in higher education institutions are persistent worldwide. The objective of this research is to define alternatives to mitigate risks, vulnerabilities and threats in a remote laboratory for the management of information of students, teachers and administrators in a higher education institution. The deductive method and exploratory research were used with the application of seven phases defined by the authors. It resulted a simulation of the evaluation of the information security of a remote laboratory, an Architecture of a remote laboratory integrating virtual learning environments and a Model for the integration of information security in remote laboratories. It was concluded that information security analysis to mitigate risks, vulnerabilities and threats in a remote laboratory of a higher education institution is crucial to guarantee data protection, experiment management and integrity, confidentiality and availability (CIA). for information management of students, teachers and administrators; considering the optimization of administrative processes and the legal basis.